2020
DOI: 10.1093/jaocint/qsz003
|View full text |Cite
|
Sign up to set email alerts
|

Authentication of Coffea arabica Varieties through DNA Fingerprinting and its Significance for the Coffee Sector

Abstract: Background Locating the optimal varieties for coffee cultivation is increasingly considered a key condition for sustainable production and marketing. Variety performance varies when it comes to susceptibility to coffee leaf rust and other diseases, adaptation to climate change and high cup quality for specialty markets. But because of poor organization and the lack of a professional coffee seed sector, most existing coffee farms (and even seed lots and nurseries) do not know which varieties t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 27 publications
5
17
0
Order By: Relevance
“…The wild Arabica populations in the forest of western Wellega, northern Illubabor, western Bench Maji and Bale (Davis et al, 2018) will no doubt be found to represent key centers of diversity using molecular data and may help to elucidate the geneticgeographical structure of wild Arabica in Ethiopia. Consistent with other studies (Pruvot-Woehl et al, 2020;Scalabrin et al, 2020;Montagnon et al, 2021), SL-06 was found to be included in an Ethiopian cluster. We therefore suggest to include this accession in the Ethiopian Landrace accessions, instead of in the Worldwide Cultivars.…”
Section: Genetic Diversity Of South Sudan Arabicasupporting
confidence: 91%
See 2 more Smart Citations
“…The wild Arabica populations in the forest of western Wellega, northern Illubabor, western Bench Maji and Bale (Davis et al, 2018) will no doubt be found to represent key centers of diversity using molecular data and may help to elucidate the geneticgeographical structure of wild Arabica in Ethiopia. Consistent with other studies (Pruvot-Woehl et al, 2020;Scalabrin et al, 2020;Montagnon et al, 2021), SL-06 was found to be included in an Ethiopian cluster. We therefore suggest to include this accession in the Ethiopian Landrace accessions, instead of in the Worldwide Cultivars.…”
Section: Genetic Diversity Of South Sudan Arabicasupporting
confidence: 91%
“…Former studies (Anthony et al, 2002;da Silva et al, 2019;Benti et al, 2020) had proven the efficiency of SSR markers to study the genetic diversity of Arabica. In our study, we confirm that the reduced set of SSR markers established by Pruvot-Woehl et al (2020) are efficient to describe a new genetic group in Yemen (Montagnon et al, 2021) is again efficient to describe a new genetic group in this species: the South Sudan group. Scalabrin et al (2020) found the vast majority of the SNPs found were of low-frequency alleles.…”
Section: Genetic Diversity Of South Sudan Arabicasupporting
confidence: 77%
See 1 more Smart Citation
“…The only allotetraploid is C. arabica L. with 2n = 4x = 44 [12], which was originated from the natural cross between Coffea eugenioides S. Moore and C. canephora Pierre ex A. Froehner [13], C. arabica is the only self-fertile among the other cultivated species. This specie is genetically less diverse when compared to the diploid species [14,15], a situation that has been associated with its susceptibility to the common coffee diseases [16].…”
Section: Genetic Diversity Of Coffea Arabica Lmentioning
confidence: 99%
“…A broader study of the diversity and fingerprinting of Arabica coffee accessions from various producing regions of the world was done in 2533 genotypes [107]. These genotypes corresponding to the Core Collection of the germplasm of the Tropical Agricultural Research and Higher Education Center, accessions from Southern Sudan, and cultivars/germplasm from North, Central, and South America as well as Africa and Asia.…”
Section: Genetic Diversity Based On Molecular Markersmentioning
confidence: 99%